Dynamic load balancing algorithm to minimize the makespan time and utilize the resources effectively in cloud environment. Issue 1 (2nd January 2020) - Kumar, Mohit; Sharma, S. C.
ABSTRACT: Cloud computing is a service model in which users get on-demand service pay per use basis over the internet through some well-formed web-based tool and application. Number of applications and users are increasing frequently in cloud environment, due to which load balancing has become a critical problem for cloud service provider. There are many load balancing algorithms proposed for cloud computing in last decade, but none of the algorithms provide the elasticity and resource utilization with load balancing. Therefore, we proposed a cloud resource broker that distributes the load among all the virtual machines (VM) fairly. We have developed a dynamic load balancing algorithm that not only utilizes the cloud resources properly and reduces the makespan time of tasks, but also provides the elasticity in cloud environment. Calculated results prove that developed algorithm performs better than the existing algorithms in literature like Min-Min, SJF, and FCFS.